Evaluación de las alteraciones biomecánicas de la neuroplasticidad maladaptativa en pacientes con hemiplejia del hospital Teodoro Maldonado Carbo durante el periodo de octubre del 2018 a febrero del 2019. - Ponce Ordoñez, Jonathan Alexander (2019)
Hemiplegia is the atrophy of the hemibody (either left or right depending on the site of the lesion) resulting from a vascular brain or trauma event, in which abnormal patterns of movement and gait are present, impeding the correct mobility Patient's functional. This work was carried out research whose objective was to determine how it affects the neuroplasticity maladaptativa patients hemipléjicos attended in the area of Fisiatr The Hospital Teodoro Maldonado Carbo "IESS". Composed of 80 patients aged between 34 - 85 who responded to the inclusion criteria considered a non-probabilistic sample, with a design no experimental, transversal quantitative approach and descriptive. Results were obtained that 66% of patients do not maintain the balance in gait, 59% maintain spasticity in the affected members, adopting inadequate postures, 66% have anterior displacement of the body, and 100% of these present shoulder Descended. In conclusion, the neuroplasticity maladaptativa leads to the vulnerability of the brain before a damage, patients present with compensation postural and biomechanical that alter the realization of their activities of daily living, They adopt bad postures in static and dynamic, losing balance and coordination.